Higher diffusion in striatum and lower fractional anisotropy in white matter of methamphetamine users - Alicata, Daniel (2009)
Methamphetamine (METH) users showed structural and chemical abnormalities on magnetic resonance (MRI) studies, particularly in the frontal and basal ganglia brain regions. Diffusion tensor imaging (DTI) may provide further insights regarding the microstructural changes in METH users. We investigated diffusion tensor measures in frontal white matter and basal ganglia of 30 adult METH users and 30 control subjects using a 3 T MR scanner. Compared with healthy control subjects, METH users showed lower fractional anisotropy (FA) in right frontal white matter, and higher apparent diffusion coefficient (ADC) in left caudate and bilateral putamen. Higher left putamen ADC was associated with earlier initiation of METH use, greater daily amounts, and a higher cumulative lifetime dose. Similarly, higher right putamen ADC was associated with greater daily amounts and a higher cumulative lifetime dose. The lower FA in the right frontal white matter suggests axonal injury in these METH users. The higher ADC in the basal ganglia suggests greater inflammation or less myelination in these brain regions of those with younger age of first METH use and greater METH usage.